Pengembangan Modul Program Linear Berbasis Konstruktivisme untuk Siswa Prakerin: Development of Linear Program Module Constructivism-Based for Industrial Practice Work Student - Slamet Ngadino; Kamid Kamid; Syaiful Syaiful (Universitas Jambi, 2021)
Mathematics modules should have self-instructional, self-contained, stand-alone, adaptive, and user-friendly characteristics and be able to describe students' knowledge construction processes in studying teaching materials through modules. This development research adopts the ADDIE theory. The resulting product is a constructivism-based mathematics module for internship students. The validation results of material and design experts stated that the resulting product was excellent. Data were also obtained from small and large group instrument questionnaires and the results of assignments and linear program formative tests. The results of the XI Marketing 1 class module assignment with 35 students for the KKM 70 mathematics subject are completeness of 74.3%; unfinished 25.9%. Formative test results for class XI Marketing 1 Linear Program with 35 KKM 70 students in the learning process using the module obtained an average value of 72.43; complete 77.1%; incomplete 22.9%. Formative test results for class XI Marketing 2 with a total of 35 students in the KKM 70 learning process using textbooks obtained an average score of 60 with 54.3% complete and 44.7% incomplete. Learning using the Constructivism-Based Linear Programming module is more effective and can form student independence.